Response of soil pH to biochar application in farmland across China: a meta-analysis - Jia Yao; Xueren Wang; Mei Hong; Hui Gao; Shixiang Zhao (PeerJ)
Background Biochar, an alkaline material derived from agricultural and forestry waste, can ameliorate soil quality by adjusting soil pH. However, various types of biochar have distinct effects on soil pH due to diversity in feedstock type, pyrolysis temperature, and application rate. Method Therefore, a meta-analysis was conducted with 598 paired comparisons obtained from 104 published studies (January 2010–July 2022) to comprehensively depict the response of soil pH to biochar in farmland systems across China. Result The results showed that adding biochar significantly increased the acid soils’ pH. Still, its effects on neutral and alkaline soils varied depending on the biochar’s pH and the soil’s initial pH. The pH of acid and neutral soils was raised by 5–10% straw biochar (600–800 °C and 400–600 °C, respectively). In alkaline soils, 5–10% other biochar (200–400 °C) raised pH, while 1–5% straw biochar (200–400 °C) reduced it. The findings underscore the importance of biochar pH and initial soil pH in the divergent consequences of biochar application in farmland systems, and both factors should be considered to choose the optimal biochar type for acid, neutral, and alkaline soils.